2019
DOI: 10.1177/1354816619837111
|View full text |Cite
|
Sign up to set email alerts
|

The “Hallyu” phenomenon: Utilizing tourism destination as product placement in K-POP culture

Abstract: This article examines the effect of the Korean pop culture phenomenon also known as “Hallyu” on the inbound tourism demand of Korea. “Hallyu” products are exported throughout Asia and have been growing over the past decade. Using a Bayesian autoregressive model, we empirically investigate the product placement effects of “Hallyu” explained by the parasocial theory of previous literature utilizing inbound tourist data and show that “Hallyu” effects are also present in the overall tourism industry of Korea. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Research on tourism demand in Asia and the Pacific has generally focused on Australia (Kulendran and Dwyer 2009;Van De Vijver et al 2016;Shafiullah, Okafor, and Khalid 2019), New Zealand (Lim, Min, and McAleer 2008;Lennox 2012), Hong Kong (Song, Wong, andChon 2003;Song et al 2010aSong et al , 2010b, China (Lin et al, 2015;Li et al 2018;Xu et al 2018;Tang et al 2019), Korea (Li, Park, and Seo 2011;Seo and Kim 2019), Japan (Kuo, Liu, and Chen 2014;Chi et al 2019), Pakistan (Meo et al 2018), and the ASEAN countries (Ramos, Untong, and Kaosa-ard 2017). A few studies (Croes and Vanegas 2005;Ridderstaat et al 2014;Ridderstaat and Croes 2017) have examined the tourism demand models in the Caribbean small island developing states.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research on tourism demand in Asia and the Pacific has generally focused on Australia (Kulendran and Dwyer 2009;Van De Vijver et al 2016;Shafiullah, Okafor, and Khalid 2019), New Zealand (Lim, Min, and McAleer 2008;Lennox 2012), Hong Kong (Song, Wong, andChon 2003;Song et al 2010aSong et al , 2010b, China (Lin et al, 2015;Li et al 2018;Xu et al 2018;Tang et al 2019), Korea (Li, Park, and Seo 2011;Seo and Kim 2019), Japan (Kuo, Liu, and Chen 2014;Chi et al 2019), Pakistan (Meo et al 2018), and the ASEAN countries (Ramos, Untong, and Kaosa-ard 2017). A few studies (Croes and Vanegas 2005;Ridderstaat et al 2014;Ridderstaat and Croes 2017) have examined the tourism demand models in the Caribbean small island developing states.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Country images can be developed with several image objects, including not only specific products but also celebrities and culture (Mossberg and Kleppe, 2005). Popular media culture, including movies, dramas and music, enhances foreign media consumers' perception of the target country's image (Seo and Kim, 2020;Lee et al, 2015aLee et al, , 2015b survey of 2,836 foreigners found that their sense of the likability of Korean culture positively influenced their perception of the county's image. Furthermore, consumers who had been exposed to and enjoyed K-pop culture demonstrated a robust preference for various Korean products (Yu et al, 2014).…”
Section: K-culture Attachment and Korea's Country Imagementioning
confidence: 99%
“…80 percent of the 24 billion views of music videos by the top 200 K-pop artists on YouTube came from outside of South Korea in 2016 (Kim, 2017). During Hallyu 2.0 phase, Hallyu has cultivated into more diverse fields such as online games, beauty products, fashion, and life styles along with music and films (Seo & Kim, 2020). The examples of Hallyu contents are listed in Table 1.…”
Section: The Hallyumentioning
confidence: 99%